Affinités électives de la littérature espagnole avec la philosophie - Thierry Nallet (Cahiers de Civilisation Espagnole Contemporaine)
The relations between the Spanish and philosophy have always been complex. This article aims to take up the traditional interpretation that philosophy plays a key role in Spanish literature. Starting off from affirmations made by Miguel de Unamuno and María Zambrano, it’s clear that the literature of ideas, the essay or the philosophical novel contain rather original truths and philosophical notions. The examples chosen here are taken from philosophical essays with a strong literary component coming from José Antonio Marina and above all from the narrative opus of Álvaro Pombo. Working from a phenomenologist’s viewpoint, Pombo takes up questions related to man’s existence and ethics, in such a way that, as Hume thought, imagination and fiction seem to have shined a new light on life and the world while providing a source of casuistry to philosophers.